A Case of Phacomatosis Pigmentokeratotica Associated With Multiple Basal Cell Carcinomas. (February 2018) - Loh, Seung-Hee; Lew, Bark-Lynn; Sim, Woo-Young
Abstract : Abstract: Phacomatosis pigmentokeratotica is a recently identified disease characterized by the coexistence of an epidermal nevus with sebaceous differentiation arranged along Blaschko lines and a speckled lentiginous nevus showing a checkerboard pattern, mostly in association with various extracutaneous defects. A 52-year-old man presented with asymptomatic ulcerative plaque on his left side of perioral area. A 2 × 2-cm–sized fleshy colored ulceration on his left perioral area was consistent with basal cell carcinoma with nevus sebaceous. Next to the ulceration, there was a light pinkish to fleshy colored papule on his left cheek that showed syringocystadenoma papilliferum. On his chin area, there was a 2 × 0.3-cm–sized skin colored papule that was consistent with trichilemmoma. Moreover, various sized light brownish macules and dark brownish papules were also located on his left side of the chest wall, back, and arm. Biopsy specimens from macules on the left side of the trunk confirmed the clinical diagnosis of speckled lentiginous nevus and multiple black papules beside that a speckled lentiginous nevus also revealed basal cell carcinomas. Herein, we present a rare case of a patient with phacomatosis pigmentokeratotica who had no extracutaneous abnormalities and who developed basal cell carcinoma, syringocystadenoma papilliferum, and trichilemmoma in nevus sebaceous on the face and speckled lentiginous nevus on the trunk. This syndrome needs adequate follow-up due to the possibility of malignant transformation.